2002
DOI: 10.1128/jvi.76.8.4119-4124.2002
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intramolecular Recombinations in theCucumber Mosaic VirusGenome Related to Adaptation to Alstroemeria

Abstract: In four distinct alstroemeria-infecting cucumber mosaic virus (CMV) isolates, additional sequences of various lengths were present in the 3 nontranslated regions of their RNAs 2 and 3, apparently the result of intra-and intermolecular recombination events. Competition experiments revealed that these recombined RNA 2 and 3 segments increased the biological fitness of CMV in alstroemeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 42 publications
1
33
0
1
Order By: Relevance
“…They suggested that after synthesis of a complete copy of minus-strand RNA5, the replicase would switch to the minus-strand promoter located in the TLS at the 39 end of the CMV RNAs. This is consistent with the recombinant Alstroemeria-CMV isolates (Chen et al, 2002), but is not compatible with the recombinants observed here or in other publications (de Wispelaere et al, 2005;Fernandez-Cuartero et al, 1994;Masuta et al, 1998;Suzuki et al, 2003) since none contained a duplication of the TLS, as was reported by de Wispelaere & Rao (2009). Instead, all crossover sites on I17F-CMV (RNA3 or RNA1) were located 59 of the TLS, primarily at the hotspot at or near SLG.…”
Section: Mechanism Of Recombination That Produces Aberrant Cucumovirasupporting
confidence: 71%
See 1 more Smart Citation
“…They suggested that after synthesis of a complete copy of minus-strand RNA5, the replicase would switch to the minus-strand promoter located in the TLS at the 39 end of the CMV RNAs. This is consistent with the recombinant Alstroemeria-CMV isolates (Chen et al, 2002), but is not compatible with the recombinants observed here or in other publications (de Wispelaere et al, 2005;Fernandez-Cuartero et al, 1994;Masuta et al, 1998;Suzuki et al, 2003) since none contained a duplication of the TLS, as was reported by de Wispelaere & Rao (2009). Instead, all crossover sites on I17F-CMV (RNA3 or RNA1) were located 59 of the TLS, primarily at the hotspot at or near SLG.…”
Section: Mechanism Of Recombination That Produces Aberrant Cucumovirasupporting
confidence: 71%
“…Moreover, it has been reported as a hotspot for viral recombination between CMV RNA3 and TAV RNAs 1 and 2 (Suzuki et al, 2003) or TAV RNA3 (de Wispelaere et al, 2005), between TAV RNA3 and CMV RNAs 1 and 2 (Shi et al, 2007), and in Q-CMV (subgroup II) intragenomic recombinants (de Wispelaere & Rao, 2009). Finally, this was also the crossover site observed in the natural recombinant Alstroemeria-CMV (Chen et al, 2002), and in certain TAV strains (Moreno et al, 1997;Raj et al, 2007Raj et al, , 2009). …”
Section: Discussion Effects Of 6 Nt Deletions In I17f-cmv Rna3mentioning
confidence: 99%
“…In addition, more than one-third of the R-CMV/P-TAV recombinants were of an aberrant type, resulting in a 160-180 nt duplication in the 39 NCR (de Wispelaere et al, 2005). As similar recombinants have also been observed in certain natural CMV and TAV isolates (Chen et al, 2002;Moreno et al, 1997), it is surprising that this type of recombinant was not detected in the present study, but this may be due to the instability in tobacco plants of I17F-CMV/R-CMV recombinants of this type (Pierrugues et al, 2007).…”
Section: Discussionmentioning
confidence: 74%
“…Focusing on the family Bromoviridae, reports include recombination events in members of the genera Cucumovirus (Férnandez-Cuartero et al, 1994;Fraile et al, 1997;Roossinck et al, 1999;Chen et al, 2002;Bonnet et al, 2005) and Bromovirus (Bujarski & Kaesberg 1986;Allison et al, 1990), as well as between viruses belonging to different genera (de Wispelaere et al, 2005). Phylogenetic trees for proteins were obtained using the PHYML program implemented in PROTTEST that builds the best tree under the best molecular evolutionary model.…”
Section: Introductionmentioning
confidence: 99%